2020
DOI: 10.3389/fpsyg.2020.01299
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Self-Determination Theory-Based Measure of Motivation to Exercise and Diet in Children

Abstract: To develop and test the factorial structure of a new self-determination theory-based measure of behavioral regulation in children. Methods: Five hundred ninety 590 (F = 51.7%) children aged 7 to 11 years completed the Motivation to Exercise and Diet (MED-C) questionnaire, which comprises 16 items (eight for exercise and eight for diet) grouped into eight factors (five motivations and three needs). Psychometric testing included confirmatory factor analysis and internal consistency. Measurement invariance analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 109 publications
0
20
0
2
Order By: Relevance
“…In this scenario, a supportive relationship with parents can help to buffer stressful experiences. Parents are often essential role models for eating behaviours and physical exercise aptitudes in children [ 1 , 3 ], and good parenting skills become particularly crucial during an early stage in life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, a supportive relationship with parents can help to buffer stressful experiences. Parents are often essential role models for eating behaviours and physical exercise aptitudes in children [ 1 , 3 ], and good parenting skills become particularly crucial during an early stage in life.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood obesity and accompanied disordered eating attitudes and behaviours are some of the most significance health challenges of the twenty-first century [ 1 , 2 , 3 ]. Research has consistently revealed that childhood obesity and disordered eating attitudes are each associated with numerous physical health issues that track into adulthood, as well as the increased risk of developing eating disorders (EDs), including anorexia nervosa (AN), bulimia nervosa (BN) and binge eating disorder (BED) [ 4 ], during adolescence [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Model comparisons were performed to exclude factorial structures different than the original one (Milavic et al, 2019;Rossi and Mannarini, 2019;Pietrabissa et al, 2020a). Specifically, the following were tested: (A) a single-factor modelspecifying a single dimension called "Dispositional Forgiveness"; (B) a three-factor first-order model-specifying three simple first-order factors called "Self, Other, and Situation"; (C) a second-order model (hierarchical) with a general secondorder factor and three first-order factors respectively called "Dispositional Forgiveness, Self, Other, and Situation"; and (D) a second-order model (hierarchical) retracing the hypothesized original model without "positive" and "negative" valence factors (graphical representation of these models were reported in the Supplementary Material 1).…”
Section: Resultsmentioning
confidence: 99%
“…The item pool for the CPI-HP was developed using a three-step double-blind study procedure—already employed in other studies (Simpson et al, 2018 ; Milavic et al, 2019 ; Pietrabissa et al, 2020a , b ).…”
Section: Studymentioning
confidence: 99%